Acute psycho-physiological responses to perceptually regulated hypoxic and normoxic interval walks in overweight-to-obese adults. Issue 5 (May 2021) - Hobbins, Liam; Girard, Olivier; Gaoua, Nadia; Hunter, Steve
Abstract: Objectives: We investigated psycho-physiological responses to perceptually regulated interval walks in hypoxia versus normoxia in obese individuals. Design: Within-participants repeated measures. Methods: Ten obese adults (BMI = 32 ± 3 kg/m −2 ) completed a 60-min interval session (15 × 2 min walking at a rating of perceived exertion of 14 on the 6–20 Borg scale with 2 min of rest) either in hypoxia (FiO2 = 13.0%, HYP) or normoxia (NOR). A third trial replicating the HYP speed pattern was carried out in normoxia as a control (CON). Exercise responses were analysed comparing the average of 1st to 3rd exercise bouts to those of the 4th–6th, 7th–9th, 10th–12th and 13th–15th exercise bouts (block 1 versus 2, 3, 4 and 5). Results: Treadmill speed was slower during block 4 (6.14 ± 0.67 versus 6.24 ± 0.73 km/h −1 ) and block 5 (6.12 ± 0.64 versus 6.25 ± 0.75 km/h −1 ) in HYP compared to NOR or CON (p = 0.009). Compared to NOR and CON, heart rate was +6–10% higher (p = 0.001), whilst arterial oxygen saturation (−12–13%) was lower (p < 0.001) in HYP. Perceived limb discomfort was lower in HYP and CON versus NOR (−21 ± 4% and −34 ± 6%; p = 0.004). Conclusions: In overweight-to-obese adults, perceptually regulated interval walks in hypoxia versus normoxia leads to progressively slower speeds along with lower limb discomfort and larger physiological stress than normoxia. Walking at the speed adopted in hypoxia produces similar psycho-physiological responses at the same absolute intensity in normoxia.